Aplikasi Pengelolaan Data Tools Menggunakan Delphi XE2 di PT. Torishima Guna Engineering Kab Sukabumi - WAWANG ADI DARMA (LP2M CBI PRESS, 2018)
Information Systems data processing storage of goods / tools is one part in a company that is urgent, goods / work tools is a very important element that can not be separated because it can help facilitate the workers in doing the job properly and correctly. The use of a large number of tools and users of the tool also allows many of the occurrence of data collection errors and result in loss of equipment and goods PT. Torishima Guna Engineering Sukabumi district is a company located inSukabumi. The data management of the goods / work aids has not used a good and accurate system, still using a manual system, where every item / equipment borrowed, returned, lost or damaged is still manually recorded every day. This resulted in the late reporting of data goods / tools (work tools) that exist in the company. The author tries to do research and build a system using Delphi XE2 program to handle the problem